Stimulus strength determines the BTK-dependence of the SHIP1-deficient phenotype in IgE/antigen-triggered mast cells. Issue 1 (December 2018) - Zorn, Carolin; Simonowski, Anne; Huber, Michael
Abstract Antigen (Ag)-mediated crosslinking of IgE-loaded high-affinity receptors for IgE (FcεRI) on mast cells (MCs) triggers activation of proinflammatory effector functions relevant for IgE-associated allergic disorders. The cytosolic tyrosine kinase BTK and the SH2-containing inositol-5′-phosphatase SHIP1 are central positive and negative regulators of Ag-triggered MC activation, respectively, contrarily controlling Ca2+ mobilisation, degranulation, and cytokine production. Using genetic and pharmacological techniques, we examined whether BTK activation inShip1 −/− MCs is mandatory for the manifestation of the well-known hyperactive phenotype ofShip1 −/− MCs. We demonstrate the prominence of BTK for theShip1 −/− phenotype in a manner strictly dependent on the strength of the initial Ag stimulus; particular importance for BTK was identified inShip1 −/− bone marrow-derived MCs in response to stimulation with suboptimal Ag concentrations. With respect to MAPK activation, BTK showed particular importance at suboptimal Ag concentrations, allowing for an analogous-to-digital switch resulting in full activation of ERK1/2 already at low Ag concentrations. Our data allow for a more precise definition of the role of BTK in FcεRI-mediated signal transduction and effector function in MCs. Moreover, they suggest that reduced activation or curtate expression of SHIP1 can be compensated by pharmacological inhibition of BTK andvice versa .